(Democratic) regime change and the representation of women in parliament. Issue 3 (2nd September 2017) - Stockemer, Daniel; Kchouk, Bilel
ABSTRACT: A regime change not only rests on new rules and political opportunities, but also it may bring alternatives in the distribution of power and representation of groups. The installation of a new regime, in particular, a regime change from autocracy to democracy, could also be beneficial for the representation of women in parliament. Including women in the country's positions of power could be a sign of openness in the political arena, could provide legitimacy to the new regime and might stand for a new set of values. In this paper we measure the degree to which women's representation changes after a regime transition, in particular, from autocratic to democratic rule, but also reciprocally. Using a global dataset on women's representation from 1946 to 2014 including more than 140 regime changes, we establish through descriptive and inferential statistics that most regime changes, regardless of the nature of the transition involved, do not improve the representation of women.